Pengaruh Kualitas Produk dan Desain Produk terhadap Volume Penjualan pada UD. Sinar Arafah Jaya di Deli Serdang - Muhammad Rohim Adamhuri; Khafi Puddin (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research is motivated to decreased volume at UD. Sinar Arafah Jaya in Deli Serdang. The decrease in sales volume indicates there are factors influence sales. Referring to previous studies as empirical studies. The level of sales volume is thought to be influenced by various factors such as quality and product design. The purpose of this study is test the effect of product quality and product design on sales volume at UD. Sinar Arafah Jaya products. This study uses a mixed methods (a mix of quantitative and qualitative). Collected data using questionnaire and interview. Respondents in this study were 32 people consumers who had purchased UD. Sinar Arafah Jaya products. The hypothesis was formulated and tested using regression analysis with SPSS software. While qualitative analysis was obtained from the results of interview transcripts with owner which processed with NVivo 12 Pro software and provided information and explanations. The results of quantitative research show that, simultaneously, quality and product design have a positive and significant effect on sales volume (f count 58,333 > f table 8,183 with a significant value of 0.000 < 0.05). Then the results of qualitative research also show that sales volume is influenced by quality and product design, various other aspects such as promotional strategies, pricing, and distribution channels. All of elements support each other to achieve the maximum sales volume target.